Analysis Of The Constraints Perceived By Sheep Farmers In Jammu And Kashmir - Hussain, Khalid; Chander, Mahesh; Hari, R.; Chaturvedani , A.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to analyze the constraints perceived by sheep farmers in sub tropical zone of Jammu and Kashmir. One hundred and twenty sheep rearing farmers were randomly selected from four blocks of Rajouri and Poonch districts of Jammu and Kashmir. Pretested structured interview schedule was used to analyze their constraint levels and the results were expressed in total weighted mean scores and ranked accordingly. The results revealed that inadequate credit facilities, lack of knowledge in scientific practices, poor services and facilities provided by the government, inadequate technical guidance, non-availability of training facilities, non-availability of roughage, lack of veterinary services at farmer’s door step and non-availability of organized market for wool/mutton were the major constraints faced by the respondents in the study area. The study highlights the need to formulate schemes to alleviate these constraints so as to empower the farmers of this region.